Study on Demand for Skilled Labor in Unregistered MSMEs of India - Sinha, Shabnam; Pental, Kartik (World Bank, Washington, DC, 2017)
This report seeks to highlight the economic importance of unregistered Micro Small and Medium Enterprises (MSMEs) in India and ascertain their role in the job market. It attempts to summarize the sector’s demand for skilled labor and entrepreneurial skills training.The report opens with an executive summary of key findings and a background explaining the context in which it has been prepared and the research objectives it seeks to fulfil. The next section of the reportpresents key insights derived from the analysis of data collected through the Unregistered MSMEs censusof 2006-07 and the associated extrapolations made by the government in 2013-14. This section discusses the size, scale and profile of the unregistered MSME sector along with estimates of the employment generated by the sector. This is followed by a section on insights from field based research in Chhattisgarh. It utilizes primary datato estimate how the unregistered MSME sector has grown in the state; how its profile and scale hasevolved since the census of 2006-07; the size of the labor force engaged by unregistered businesses in Chhattisgarh; the sector’s demand for skilled labor; its preference for formally skilled/certified employees; the wage gains that employees can expect to derive from obtaining formal skills certification;its contribution to the state economy; and the skills training needs of entrepreneurs. The next section of the report builds on the findings of the first two sections to estimate and present national level aggregates for the growth of the unregistered MSME sector, the quantum of labor force employed by unregistered MSMEs in India, the sector’s demand for skilled labor and the wage benefitsthat employees can derive from attaining formal skills certification.This is the most recent and holistic data source available as thenext unregistered MSME census is currently in the planning and data collection phase. Primary data fromthe low-income state of Chhattisgarh has been used to adjust/control the extrapolations made using the2006-07 census data. Extrapolations have been made based on gross state domestic product per capita,change in gross state domestic product per capita, female labor force participation estimates and change infemale labor force participation estimates.The report closes with a set of recommendations directed at strengthening policy and programmingresponse to the skills training needs of unregistered MSMEs in India. It presents ideas that different tiersof governance, skills training providers and skill development agencies can leverage upon to realize theobjectives of the ‘Skill India Mission.’State level estimates for key data points are given in Annexure I of the report and Annexure II presents the approach and methodology used to structure the field based research carried out in Chhattisgarh.